Die Fragilität des Zugangs eine Kritik der Informationsgesellschaft - Schüller-Zwierlein, André 1972- (Age of access? Grundfragen der Informationsgesellschaft, 2022)
We have made ourselves comfortable in the information society: information is available on demand, everywhere, at any time. Simultaneously, we are seeing the resurgence of populism and radicalism, violence and uninhibited communication. This book asks whether there is a construction flaw hidden in the notion of the information society itself and in the practices associated with it that fosters populism and radicalism